2010
DOI: 10.1007/s00508-010-1426-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum anti-mullerian hormone in adolescent and young adult Chinese patients with polycystic ovary syndrome

Abstract: Serum AMH levels are elevated in adolescent and young adult Chinese patients of PCOS. Serum AMH measurement offers a relatively poor diagnostic potency with a sensitivity of 61.7% and a specificity of 70% at 8 ng/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 25 publications
4
25
1
1
Order By: Relevance
“…Our findings were compatible with the previously published literature, showing that serum AMH levels are slightly higher in females with PCOS [20] and that a significant positive correlation between serum AMH and HOMA-IR levels is present in these adolescents [21]. The present study also indicates that insulin may have a direct effect on AMH synthesis in granulosa cells.…”
Section: Discussionsupporting
confidence: 95%
“…Our findings were compatible with the previously published literature, showing that serum AMH levels are slightly higher in females with PCOS [20] and that a significant positive correlation between serum AMH and HOMA-IR levels is present in these adolescents [21]. The present study also indicates that insulin may have a direct effect on AMH synthesis in granulosa cells.…”
Section: Discussionsupporting
confidence: 95%
“…In recent years, AMH has been recommended for diagnosing PCOS, but in practice there are great discrepancies in the diagnostic power [17,18,24]. In the present study, the diagnostic sensitivity and specificity of AMH was not satisfying, suggesting that sole use of AMH is not adequate for diagnosing PCOS because of its low accuracy.…”
Section: Discussioncontrasting
confidence: 70%
“…According to Pigny et al [24], the diagnostic specificity reached 92 % and the sensitivity reached 67 % if a serum level of 60 pmol/L was set as the cut-off value. However, Li et al [17] reported that the diagnostic specificity was only 70 % and the sensitivity was only 61.7 % when AMH was used for the diagnosis of PCOS patients. Hart et al [13] reported that the specificity of AMH in predicting PCOS in adolescent patients was <70 % and the sensitivity was only 50 %.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, serum AMH levels increase by 2-3-fold in women with early stage PCOS compared with normal controls. The sensitivity of serum AMH for diagnosis of PCOS ranges from 64 to 99 % [60][61][62][63][64][65][66][67][68]. The wide range of sensitivities among studies is likely due to variations in diagnostic criteria and in the age of the patient population.…”
Section: Diagnosis Of Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%